2003
DOI: 10.1149/1.1572482
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Kelvin Probe Force Microscopy and Magnetic Force Microscopy for Characterization of Duplex Stainless Steels

Abstract: In this study, the Volta potential distribution over the surface of duplex stainless steels ͑DSSs͒ has been mapped for the first time with submicrometer resolution by scanning Kelvin probe force microscopy ͑SKPFM͒. The different magnetic properties of ferrite and austenite enable the utilization of magnetic force microscopy ͑MFM͒ for visualizing their surface distribution without the need of surface etching. The combined MFM and SKPFM mapping of the same area makes it possible to associate the variation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 39 publications
(95 reference statements)
5
26
0
2
Order By: Relevance
“…In general, Figure 4a shows the different tendency to corrosion of the ferrite and austenite, with ferrite expected to be more prone to corrosion (darker in Figure 4a) compared to austenite (brighter in Figure 4a). This is in agreement with previous studies where a higher susceptibility to dissolution of ferrite has been observed [8,17,18]. Moreover, a high resolution image in Figure 4b shows the Volta potential variation within a ferrite grain, with finely dispersed quenched-in Cr 2 N exhibiting higher Volta potential (nobler) than the ferrite matrix.…”
Section: Kfm Characterizationsupporting
confidence: 92%
“…In general, Figure 4a shows the different tendency to corrosion of the ferrite and austenite, with ferrite expected to be more prone to corrosion (darker in Figure 4a) compared to austenite (brighter in Figure 4a). This is in agreement with previous studies where a higher susceptibility to dissolution of ferrite has been observed [8,17,18]. Moreover, a high resolution image in Figure 4b shows the Volta potential variation within a ferrite grain, with finely dispersed quenched-in Cr 2 N exhibiting higher Volta potential (nobler) than the ferrite matrix.…”
Section: Kfm Characterizationsupporting
confidence: 92%
“…7(b) and (c) with ferrite (a) and austenite (c) phases marked. This is a well recorded phenomenon in duplex stainless steels in chloride bearing solutions and is caused by a galvanic couple that forms between the two phases as a result of chemical partitioning; Cr, Mo, W concentrating in ferrite and Ni, N in austenite (Ref [14][15][16][17]. The high nickel and nitrogen give austenite a more noble potential in chloride solutions making it the cathode to the more negative ferrite (the anode).…”
Section: Corrosion Morphologymentioning
confidence: 99%
“…Importantly, the VPD observed was an effective indicator of how corrosion developed due to microstructural features. Subsequent to these findings, several research groups [31][32][33][34][35][36][37][38][39] have been able to verify that SKPFM is both reliable and effective in characterizing various alloy systems to accurately explain corrosion initiation behavior.…”
Section: Discussionmentioning
confidence: 95%